Morphology and Crystallinity Study of Sago Starch-Based Degradable Plastic with Chitosan and Calcium Carbonate as Additives - Rozanna, Dewi; Zulnazri, B.; Novi Sylvia, C.; Iqbal Kamar, D.; Medyan Riza, E. (INTI International University, 2023)
To reduce the consumption of synthetic polymers, researchers have studied the use of carbohydrates, lipids, proteins and composites to generate biodegradable plastic. In this study, degradable plastic from sago starch modified with prepolymer polyurethane synthesized from diphenylmethylene diisocyanates and polyol with the addition of chitosan as additive and polypropylene or polyethylene as matrix was produced. The research method conducted were consisting of several stages, preparation of thermoplastic starch, blending thermoplastic starch with polypropylene or polyethylene, synthesis of degradable plastic and irradiation process. Thermoplastic starch was characterized using Scanning Electron Microscopy-Energy Dispersive X-Ray (SEM-EDX) and X-Ray Diffraction (XRD). SEM-EDX to study surface morphology, meanwhile XRD to determine the crystallinity of thermoplastic starch. The SEM analysis of 5000x magnification showed the presence of many material elements in the thermoplastic starch matrix that are visible on the entire surface of the plastic. The results of EDX analysis revealed the presence of chemical elements such as carbon, oxygen, magnesium, calcium, titanium, palladium, gold, and carbon dioxide. These elements came from the thermoplastic starch made from sago which contains magnesium (iron), calcium and the main additive CaCO3. From the XRD analysis results, it can be shown that thermoplastic starch was amorphous and crystalline. XRD analysis of thermoplastic starch has a low crystallinity value at 26.85140 .